Atypical Pyoderma Gangrenosum with Ulcerative Colitis treated successfully with prednisolone and mesalazine: A case report - Doaa AE Abou-Taleb; Mahmoud F Sherif; Ahmed S Mohammed (Global Journal of Medical and Clinical Case Reports - Peertechz Publications, 2021)
Introduction: Pyoderma Gangrenosum (PG) manifests as recurrent deep ulceration of the skin and PG is often associated with a variety of systemic diseases, such as Inflammatory Bowel Diseases (IBD), inflammatory arthropathies, hematologic malignancies and hepatitis. There has been neither laboratory finding nor histological feature diagnostic of PG, and diagnosis of PG is mainly made based on the exclusion criteria. Patient and methods: A male patient 21 years old, complained of rectal bleeding of 3 weeks duration. He presented with a large, painful and rapidly progressive cutaneous ulcer in the right flank. Laboratory and microbiological investigations, colonoscopic biopsy and a skin biopsy from the ulcer were performed.  Results: An atypical presentation of PG with Ulcerative Colitis (UC) was diagnosed. The PG rapidly resolved after starting treatment with prednisolone and mesalazine and the ulcer healed with scar. After successful treatment the patient suddenly stopped all his treatment and he came back again with rectal bleeding and a rounded, painful and rapidly progressive cutaneous ulcer in each cheek. One month after starting prednisolone and mesalazine treatment, complete healing of both ulcers has occurred. Conclusion: A rare atypical presentation of PG with risk of misdiagnosis and the rapid healing of PG with combination of prednisolone and mesalazine therapy were concluded.